The effects of pumping on the air content and void structure of air-entrained, wet mix fibre reinforced shotcrete. (December 2019) - Talukdar, S.; Heere, R.
Abstract: The air content and void structure of hardened shotcrete is essential for its durability and resistance against freeze thaw damage. However, producing a mix which is pumpable, shootable, and also meets durability requirements is not always easy. The situation is further complicated when adding fibres to the mix. This paper presents some observations concerning air content and air void systems of fresh and hardened fibre reinforced shotcrete mixes used for a ground support project in Western Canada. The most critical findings were that altering the time the mix spends in the line and presumably while under pressure may affect the overall air content and the air void structure of the hardened material, and that the pumping process itself has an adverse effect on the total air content and spacing factor in the hardened material.